Meningkatkan Kemampuan Mahasiswa dalam Menerapkan Keterampilan Dasar Mengajar Melalui Supervisi Klinis - Ismail, Sumarno (Jurnal Entropi, 2013)
Eight of basic skills in teaching should be practiced to the student in stage, continually, and through direct observation. Those are: (1) Open-close skill in learning, (2) Explanation skill, (3) Asking skill (4) Variation skill in learning, (5) Giving reinforcement, (6) Managing class, (7) Managing discussion, and (8) Controlling small group. There are something had identified in Student Observation Training Program (PPL) they are (a) Minimity of leader students in guidance, (b) Students unablenes in determining their capacity of professional teaching which is done to fill the basic skill standard in teaching, and (c) there is no self discription about teaching basic skills that have been practiced by their selves. Hence, it significantly has the process of guidance through clinical supervision approach. It intends to optimize the guidance and to maximize students capacity in apply teaching skills. The result of this study proves that through clinical supervision approach increase students capacity in apply teaching skills.